In-situ injectable bone repair adhesive material with double-sequence osteogenesis promoting function as well as preparation method and application of in-situ injectable bone repair adhesive material

The preparation of sodium alginate microspheres by double chemical graft modification and microfluidic control technology of hyaluronic acid was solved, and the problem of insufficient matching and adhesion performance of bone repair materials with complex shape bone defects was achieved, and the injectable bone repair materials were achieved , UV curing, wet adhesion and dual timing promote bone function, meeting the complex needs of bone defect repair.

CN119386249AActive Publication Date: 2025-02-07ZHEJIANG UNIV

Patent Information

Application Number
CN202411302112.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-07
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing bone repair materials are difficult to match complex-shaped bone defects and lack adhesion properties and controllable timing to promote bone function.

Method used

By dual chemical graft modification of hyaluronic acid, it imparts UV curing and wet adhesion properties, and combines microfluidic control technology to prepare sodium alginate microspheres loaded with bone drugs to achieve dual timing release.

Benefits of technology

The injectable, in situ UV curing, wet adhesion and dual timing-promoting bone function of bone repair materials is achieved, meeting the complex needs of bone defect repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386249A_ABST
    Figure CN119386249A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ injectable bone repair adhesive material with a double-sequence osteogenesis promoting function as well as a preparation method and application of the in-situ injectable bone repair adhesive material. The preparation method comprises the following steps: 1) sequentially carrying out dual chemical grafting modification on hyaluronic acid by using methacrylic anhydride and dopamine hydrochloride to obtain a DA-HAMA biomacromolecule with UV curing and adhesion functions; (2) preparing a Ca < 2 + > physical cross-linked sodium alginate microsphere material loaded with an osteogenesis promoting drug by using a micro-fluidic system; and (3) preparing a DA-HAMA solution under dark and heating conditions, adding the vascular promoting factors and the drug-loaded microspheres when the DA-HAMA solution is cooled to room temperature, uniformly mixing, and carrying out centrifugal defoaming and irradiation sterilization to obtain the in-situ injectable bone repair adhesive material. The bone repair adhesive material has the functions of being degradable, injectable, capable of being adhered in a wet state, promoting blood vessels and promoting bone formation, and a brand new strategy is provided for bone defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation technology of a bone repair material, and in particular to an in-situ injectable bone repair adhesive material with a dual sequential osteogenesis function, a preparation method thereof and an application thereof. Background Art

[0002] The destruction of the integrity of the bone structure is called a bone defect, which is usually caused by traffic accidents, surgery and other factors. The autologous bone, titanium mesh and other materials currently used in clinical practice have problems such as the need for secondary surgery and poor biological activity. In recent years, tissue engineering technology has developed rapidly. With the advantages of being degradable and biocompatible, hydrogels and scaffold materials have been used in the treatment of bone defects. However, ordinary tissue engineering materials are difficult to match the complex and changeable shapes of bone defects, the materials do not have adhesion properties, resulting in a loose fit with the defect area and easy deviation, and the timing of the material's effect on bone repair is uncontrollable. These problems make it difficult for most existing tissue engineering materials to fully meet the complex needs of bone defect repair.

[0003] Further analysis of the above problems revealed that injectability can solve the problem of complex shapes of bone defect areas; adhesion can achieve relative fixation between the material and the defect area. Considering that the bone defect area has more tissue fluid, the adhesion needs to be upgraded to wet adhesion; in the early stage of natural bone repair, the main process is to form a vascular network to meet the blood supply needs, and the later stage is mainly for the generation of new bone. Therefore, if a new tissue engineering material can be developed that can meet the above requirements at the same time, it will have a huge driving effect on bone defect repair.

[0004] Based on this, the present invention designs an in-situ injectable bone repair adhesive material with dual sequential osteogenesis function, as well as its preparation method and application. By selecting hyaluronic acid as the main raw material, double chemical grafting modification is performed on it to give it UV curing and wet adhesion properties, and at the same time designing a method of directly loading angiogenic drugs and physically cross-linking sodium alginate to load osteogenic drugs, the purpose of dual sequential release is achieved, providing a new treatment strategy for bone defect treatment. Summary of the invention

[0005] The purpose of the present invention is to provide an in situ injectable bone repair adhesive material with dual sequential osteogenesis function and its preparation method and application to address the problems of traditional bone repair materials being ineffective and inconvenient to use. The bone repair adhesive material is degradable, injectable, wet-adhesive, and has the functions of promoting blood vessels and promoting osteogenesis, providing a new strategy for bone defect repair.

[0006] The present invention is implemented by the following technical solution, and the specific steps include:

[0007] A method for preparing an in-situ injectable bone repair adhesive material with dual sequential osteogenesis function comprises the following steps:

[0008] 1) Hyaluronic acid is double-grafted and modified with methacrylic anhydride and dopamine hydrochloride in sequence to obtain DA-HAMA biomacromolecules with UV curing and adhesion functions;

[0009] 2) Preparation of Ca using microfluidic system 2+ Physically cross-linking sodium alginate microspheres, placing them in an osteogenic drug solution for immersion and adsorption to obtain drug-loaded microsphere materials;

[0010] 3) preparing a DA-HAMA solution, adding angiogenic factors and the drug-loaded microspheres to the solution when the solution is cooled to room temperature, and mixing them evenly. After centrifugal degassing and irradiation sterilization, an in situ injectable bone repair adhesive material is obtained.

[0011] Furthermore, in step 1), the double chemical grafting modification of hyaluronic acid using methacrylic anhydride and dopamine hydrochloride in sequence is specifically that methacrylic anhydride is firstly used to modify hyaluronic acid to obtain HAMA, and then dopamine hydrochloride is used to modify HAMA.

[0012] Furthermore, in the process of modifying hyaluronic acid with methacrylic anhydride, the hyaluronic acid is heated and dissolved in a PBS solution, methacrylic anhydride is slowly added dropwise, and after reacting for 2-3 hours, an equal volume of deionized water is added, and then hydrogen peroxide is slowly added dropwise to the solution, and after stirring for 30-60 minutes, it is dialyzed in the dark, and HAMA is obtained after freeze-drying; wherein the reaction temperature is 50-60°C, the stirring rate is 200-400r / min, the hyaluronic acid has a molecular weight greater than 100,000 and a concentration of 3-8wt%, the methacrylic anhydride is added at a concentration of 2-6wt%, and the amount of hydrogen peroxide added is 1 / 10-1 / 5 of the total volume of the solution, the deionized water is dialyzed for 5-10 days, and the solution is changed 3-5 times a day.

[0013] Furthermore, in the process of modifying HAMA with dopamine hydrochloride, the HAMA and dopamine hydrochloride are dissolved in a DMSO / deionized water mixed solvent, EDC is added under nitrogen protection and stirred for activation for 30-60 minutes, and then NHS is added for coupling reaction, and the obtained product is dialyzed in the dark and freeze-dried to obtain DA-HAMA biomacromolecules; the dopamine hydrochloride concentration is 0.2-0.8wt%; the HAMA concentration is 5-10wt%; the ratio of the mixed solvent is 10wt% DMSO / 90wt% deionized water; the EDC concentration is 0.02-0.1wt%; the NHS concentration is 0.02-0.1wt%; the coupling reaction time is 12-24 hours; the stirring adopts magnetic stirring at 400-600 rpm; after the coupling reaction, the product is dialyzed with deionized water in the dark for 5-7 days, and the liquid is changed 3-5 times a day.

[0014] Further, in step 2), the microfluidic system prepares Ca 2+ In the process of physically cross-linking sodium alginate microspheres, the microfluidic system channel diameter is 50-200 μm; the coagulation bath is 0.04-0.1 g / ml calcium chloride, and the solvent system volume ratio is 1:3-3:1 deionized water and anhydrous ethanol; the viscosity of the sodium alginate is 15-25 cP (1wt% in H 2 O), the concentration is 0.02-0.04g / ml; the extrusion rate of the microfluidic device is 0.1-1.0mL / h, the solution stirring rate is 20-40r / min, the microsphere aging time is 5-15min, the temperature is 20-25°C, the pH is 6.5-7.5, and the obtained microspheres are washed 3-5 times with deionized water, each time for 3-5min;

[0015] During the immersion adsorption process, the osteogenic drug is one or more of bone morphogenetic protein-2 (BMP-2), osteogenic growth peptide (OGP), transforming growth factor β (TGF-β), danshensu, icariin, total flavonoids of Rhizoma Drynariae, paeoniflorin and total saponins of Panax notoginseng, with a concentration of 100 ng / ml-0.1 g / ml, and the immersion adsorption time is 5-15 min. After rinsing with deionized water, the drug is air-dried and stored for later use.

[0016] Furthermore, in step 3), during the preparation of the DA-HAMA solution, the DA-HAMA solution contains a photoinitiator, and under light-proof and heating conditions, the DA-HAMA preparation temperature is 60-80° C., the concentration is 5-15wt%, the photoinitiator is one or more of LAP, Irgacure, and photoinitiator 2959, the concentration is 0.25-0.5wt%, and the solvent is PBS;

[0017] The angiogenic drug is one or more of vascular endothelial growth factor (VEGF), angiopoietin-1 (Ang-1), QK peptide, deferoxamine, salvianolic acid B, astragaloside, ginsenoside, and paeoniflorin, with a concentration of 100 ng / ml-0.1 g / ml;

[0018] The concentration of the drug-loaded microspheres is 0.5-5wt%;

[0019] During the centrifugal degassing process, the rotation speed is 500-1000 rpm for 3-10 min.

[0020] An in-situ injectable bone repair adhesive material with dual sequential osteogenesis function is obtained by using any of the above-mentioned preparation methods.

[0021] A bone repair material comprises the bone repair adhesive material.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1) The present invention uses HAMA, sodium alginate, dopamine hydrochloride, methacrylic anhydride, osteogenic drugs, angiogenic drugs, etc. as raw materials, and combines dual chemical grafting modification, blending, microfluidics technology, injectability, in-situ UV curing and other combined processes to prepare an in-situ injectable bone repair adhesive material with dual sequential osteogenic function. The above raw material selection and process combination are original to the present invention.

[0024] 2) In the present invention, the double chemical grafting modification technology is used in turn to modify hyaluronic acid to obtain DA-HAMA biomacromolecules, which can be used to prepare bone repair gel pre-solutions with injectable, in-situ UV curing and wet adhesion functions. First, hyaluronic acid, the main component of the extracellular matrix, is selected as the main chain of the macromolecule. It is widely distributed in the human body and participates in various physiological processes such as tissue hydration, wound repair, and cell migration. It is of great significance for tissue repair; secondly, methacrylic anhydride is used for the first grafting modification to give hyaluronic acid UV curing ability, combined with the high solubility of the hyaluronic acid main chain in water, the injectable performance of DA-HAMA can be guaranteed; then dopamine hydrochloride is used through EDC coupling reaction to achieve the reaction between dopamine hydrochloride and the carboxyl group on the HAMA main chain, further giving the DA-HAMA molecule wet adhesion performance.

[0025] 3) The present invention successfully prepared Ca2+3+10-carrying osteogenic drugs by microfluidics + impregnation adsorption combined process. 2+ Physically cross-linked sodium alginate microspheres provide the possibility for the second stage of double-sequential osteogenesis. 2+ Physical cross-linking molding, while Ca 2+Cross-linking is very likely to occur in solutions rich in phosphate, hydrogen phosphate, dihydrogen phosphate, etc., such as PBS, SBF, and human body fluids. 2+ Cross-linking to Ca 2+ The transfer of cross-linking with the above-mentioned phosphate, hydrogen phosphate, dihydrogen phosphate and other ions causes the originally formed microspheres to gradually dissolve, and because the concentrations of phosphate, hydrogen phosphate, dihydrogen phosphate and other ions in PBS, SBF, human body fluids, etc. are not particularly high, the dissolution rate of the microspheres is relatively slow. Therefore, it is equivalent to the applicant preparing a long-term self-dissolving drug carrier, and the osteogenic drug inside can be released for a long time as the microspheres dissolve, achieving a promoting effect on bone defect repair. Moreover, the dissolution of sodium alginate microspheres provides physical space for cell growth, further providing support for new bone formation. The above-mentioned Ca 2+ Although physically cross-linked sodium alginate microsphere materials have been widely used, the present invention is the first to use this property and organically cooperate with other materials with different drug release rates to achieve the purpose of efficient osteogenesis.

[0026] 4) The bone repair adhesive material of the present invention is injectable, UV-curable in situ, has wet adhesion, and dual-sequence osteogenesis functions, which can meet the complex requirements of bone defect repair. Among them, since the hyaluronic acid main chain has abundant carboxyl groups, it still maintains good water solubility even after being modified with methacrylic anhydride and dopamine hydrochloride, and will not physically solidify at room temperature after being dissolved into a solution, so it has good injectability and can well match bone defects of various shapes to obtain excellent filling effects; secondly, due to the modification of methacrylic anhydride, a photocurable group is introduced, and when injected into the bone defect area, in situ UV curing can be achieved; and the modification of dopamine hydrochloride introduces a catechol group, which can form good wet adhesion with tissues, keeping the solution from moving under the influence of surgery or exercise after solidification. , and it always keeps a good fit with the bone defect area. Otherwise, once the position shifts, it is very easy to cause heterotopic ossification in other areas, and the bone defect area cannot be well treated; finally, through the slow release of the angiogenic drugs in the adhesive matrix, a vascularized network is formed to meet the nutrition and vascular needs of the early stage of bone repair, and the osteogenic drugs in the sodium alginate microspheres will be slowly released as the calcium ions in the microspheres are chelated and transferred by other phosphate ions, and due to the physical barrier between the microspheres and the adhesive body, the release time of the osteogenic drugs will be later than that of the angiogenic drugs, which is consistent with the timing of natural bone repair: angiogenesis first and osteogenesis later, and angiogenesis synergistically promotes osteogenesis. It is precisely with the above-mentioned functional synergy of the bone repair composite adhesive that the ideal effect of bone defect treatment is achieved.

[0027] 5) The bone repair adhesive material of the present invention is easy to use and operate. It only needs to prepare the required gel pre-solution and perform in situ injection and curing with a sterile injection device. It is suitable for small bone defects of any shape and has obvious universality. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The present invention is a schematic diagram of the preparation process of the in situ injectable bone repair adhesive material with dual sequential osteogenesis function. DETAILED DESCRIPTION

[0029] The present invention is further described below with reference to specific examples.

[0030] Comparative Example 1:

[0031] 1) Use methacrylic anhydride to modify hyaluronic acid to obtain HAMA molecules. The specific process is as follows: under the condition of 200r / min magnetic stirring, hyaluronic acid with a molecular weight greater than 100,000 (concentration of 5wt%) is heated at 60°C and dissolved in a PBS solution, and methacrylic anhydride is slowly added until the concentration in the solution is 2.5wt%. After reacting for 3 hours, an equal volume of deionized water is added, and 1 / 10 of the total volume of the solution is slowly added with 30% concentration of hydrogen peroxide. After stirring for 60 minutes, dialyze in the dark (dialysis with deionized water for 10 days, and change the solution 4 times a day), and freeze-dry to obtain the desired HAMA.

[0032] 2) Prepare a HAMA solution (0.25 wt% LAP, solvent: PBS) with a concentration of 7.5 wt% under light-proof and 60°C heating conditions, add 300 ng / ml VEGF and mix well when cooled to room temperature to obtain a mixed solution;

[0033] 4) After degassing by low-speed centrifugation (500 rpm, 3 min), the mixed solution sterilized by irradiation, i.e., the adhesive, was injected into the bone defect area using a sterile injection device, and a handheld UV pen was used for in-situ UV curing (UV curing wavelength of 405 nm, power of 20 W, and time of 1 min) to achieve adhesion to the defect area, thereby achieving the purpose of bone repair.

[0034] The extract of the above material was prepared and co-cultured with bone marrow mesenchymal stem cells (BMSCs) for 7 days. The results of CCK-8 showed that the cell survival rate was about 89.5%; it was injected into a skull defect model, and it initially fitted well with the defect area. After surgical suture and feeding, sampling 4 weeks later found that about 50% of the gel was shifted, the bone repair effect was general, and the shifted gel led to heterotopic ossification.

[0035] Embodiment 1:

[0036] 1) Hyaluronic acid is double-grafted and modified with methacrylic anhydride and dopamine hydrochloride in sequence to obtain DA-HAMA biomacromolecules with UV curing and adhesion functions.

[0037] ① The process of methacrylic anhydride-modified hyaluronic acid is as follows: under the condition of 200r / min magnetic stirring, hyaluronic acid with a molecular weight greater than 100,000 (concentration of 5wt%) is heated at 60°C and dissolved in a PBS solution, methacrylic anhydride is slowly added until the concentration in the solution reaches 2.5wt%, and after reacting for 3h, an equal volume of deionized water is added, and 1 / 10 of the total volume of the solution is slowly added with 30% concentration of hydrogen peroxide, and after stirring for 60min, dialyzed in the dark (dialysis with deionized water for 10 days, changing the solution 4 times a day), and freeze-dried to obtain the desired HAMA.

[0038] ② The process of modifying HAMA with dopamine hydrochloride is as follows: 5wt% HAMA and 0.4wt% dopamine hydrochloride are dissolved in a 10wt% DMSO / 90wt% deionized water mixed solvent, 0.02wt% EDC is added for stirring activation for 30min under nitrogen protection and 400r / min magnetic stirring conditions, and then 0.03wt% NHS is added for coupling reaction for 24h. The obtained product is dialyzed in the dark (5 days, with the liquid changed 3 times a day), and the desired DA-HAMA is obtained after lyophilization.

[0039] 2) Preparation of Ca using microfluidic system 2+ Physically cross-linked sodium alginate microspheres (microfluidic system channel diameter 50 μm; coagulation bath 0.1 g / ml calcium chloride, solvent system volume ratio of 1:1 deionized water and anhydrous ethanol; microsphere preparation process parameters: sodium alginate viscosity 15-25 cP (1wt% in H 2 O), the concentration is 0.03g / ml, the extrusion rate of the microfluidic device is 0.3mL / h, the solution stirring rate is 40r / min, the microsphere aging time is 5min, the temperature is 25°C, the pH is 7.2, and the microspheres are washed 5 times with deionized water, each time for 3min), placed in a 300ng / ml BMP-2 solution for 10min for immersion adsorption to obtain the drug-loaded microsphere material, rinsed with deionized water and dried, and stored at 4°C for use;

[0040] 3) Prepare a 7.5 wt% DA-HAMA solution (0.25 wt% LAP, solvent: PBS) under light-proof and 60°C heating conditions, and add 300 ng / ml VEGF and 0.5 wt% drug-loaded microspheres to the solution after cooling to room temperature and mix well;

[0041] 4) After degassing by low-speed centrifugation (500 rpm, 3 min), the mixed solution sterilized by irradiation, i.e., the in situ injectable bone repair adhesive, was injected into the bone defect area using a sterile injection device, and a handheld UV pen was used for in situ UV curing (UV curing wavelength of 405 nm, power of 20 W, time of 1 min) to achieve adhesion to the defect area, thereby achieving the purpose of bone repair.

[0042] Compared with Comparative Example 1, this embodiment adds a second modification of the HAMA molecule and a drug-carrying physically cross-linked sodium alginate microsphere material.

[0043] The extract of the above material was prepared and co-cultured with BMSCs for 7 days. The results of CCK-8 showed that the cell survival rate was about 92.6% and the adhesion strength was about 32.4 kPa. It was injected into the skull defect model and fitted well with the defect area. After surgical suture and feeding, sampling 4 weeks later found that the defect area was obviously vascularized and the bone repair effect was good.

[0044] Embodiment 2:

[0045] 1) Hyaluronic acid is double-grafted and modified with methacrylic anhydride and dopamine hydrochloride in sequence to obtain DA-HAMA biomacromolecules with UV curing and adhesion functions.

[0046] ① The process of methacrylic anhydride-modified hyaluronic acid is as follows: under the condition of 200r / min magnetic stirring, hyaluronic acid with a molecular weight greater than 100,000 (concentration of 5wt%) is heated at 60°C and dissolved in a PBS solution, methacrylic anhydride is slowly added until the concentration in the solution reaches 2.5wt%, and after reacting for 3h, an equal volume of deionized water is added, and 1 / 10 of the total volume of the solution is slowly added with 30% concentration of hydrogen peroxide, and after stirring for 60min, dialyzed in the dark (dialysis with deionized water for 10 days, changing the solution 4 times a day), and freeze-dried to obtain the desired HAMA.

[0047] ② The process of modifying HAMA with dopamine hydrochloride is as follows: 5wt% HAMA and 0.4wt% dopamine hydrochloride are dissolved in a 10wt% DMSO / 90wt% deionized water mixed solvent, 0.02wt% EDC is added for stirring activation for 30min under nitrogen protection and 400r / min magnetic stirring conditions, and then 0.03wt% NHS is added for coupling reaction for 24h. The obtained product is dialyzed in the dark (5 days, with the liquid changed 3 times a day), and the desired DA-HAMA is obtained after lyophilization.

[0048] 2) Preparation of Ca using microfluidic system 2+Physically cross-linked sodium alginate microspheres (microfluidic system channel diameter 50 μm; coagulation bath 0.1 g / ml calcium chloride, solvent system volume ratio of 1:1 deionized water and anhydrous ethanol; microsphere preparation process parameters: sodium alginate viscosity 15-25 cP (1wt% in H 2 O), the concentration is 0.03g / ml, the extrusion rate of the microfluidic device is 0.3mL / h, the solution stirring rate is 40r / min, the microsphere aging time is 5min, the temperature is 25°C, the pH is 7.2, and the microspheres are washed 5 times with deionized water, each time for 3min), placed in a 300ng / ml BMP-2 solution for 10min for immersion adsorption to obtain the drug-loaded microsphere material, rinsed with deionized water and dried, and stored at 4°C for use;

[0049] 3) Prepare a 7.5 wt% DA-HAMA solution (0.25 wt% LAP, solvent: PBS) under light-proof and 60°C heating conditions, and add 300 ng / ml VEGF and 5 wt% drug-loaded microspheres to mix evenly when cooled to room temperature;

[0050] 4) After degassing by low-speed centrifugation (500 rpm, 3 min), the mixed solution sterilized by irradiation, i.e., the in situ injectable bone repair adhesive, was injected into the bone defect area using a sterile injection device, and a handheld UV pen was used for in situ UV curing (UV curing wavelength of 405 nm, power of 20 W, time of 1 min) to achieve adhesion to the defect area, thereby achieving the purpose of bone repair.

[0051] Compared with Example 1, the amount of drug-loaded sodium alginate microspheres added in this example was increased. The extract of the above material was prepared and co-cultured with BMSCs for 7 days. The results of CCK-8 showed that the cell survival rate was about 91.5%; the adhesion strength was about 28.2 kPa; it was injected into the skull defect model and fitted well with the defect area. After surgical suturing and feeding, sampling after 4 weeks found that the defect area was obviously vascularized and the bone repair effect was better than that of Example 1.

[0052] Embodiment 3:

[0053] 1) Hyaluronic acid is double-grafted and modified with methacrylic anhydride and dopamine hydrochloride in sequence to obtain DA-HAMA biomacromolecules with UV curing and adhesion functions.

[0054] ① The process of methacrylic anhydride-modified hyaluronic acid is as follows: under the condition of 200r / min magnetic stirring, hyaluronic acid with a molecular weight greater than 100,000 (concentration of 5wt%) is heated at 60°C and dissolved in a PBS solution, methacrylic anhydride is slowly added until the concentration in the solution reaches 2.5wt%, and after reacting for 3h, an equal volume of deionized water is added, and 1 / 10 of the total volume of the solution is slowly added with 30% concentration of hydrogen peroxide, and after stirring for 60min, dialyzed in the dark (dialysis with deionized water for 10 days, changing the solution 4 times a day), and freeze-dried to obtain the desired HAMA.

[0055] ② The process of modifying HAMA with dopamine hydrochloride is as follows: 5wt% HAMA and 0.4wt% dopamine hydrochloride are dissolved in a 10wt% DMSO / 90wt% deionized water mixed solvent, 0.02wt% EDC is added for stirring activation for 30min under nitrogen protection and 400r / min magnetic stirring conditions, and then 0.03wt% NHS is added for coupling reaction for 24h. The obtained product is dialyzed in the dark (5 days, with the liquid changed 3 times a day), and the desired DA-HAMA is obtained after lyophilization.

[0056] 2) Preparation of Ca using microfluidic system 2+ Physically cross-linked sodium alginate microspheres (microfluidic system channel diameter 50 μm; coagulation bath 0.1 g / ml calcium chloride, solvent system volume ratio of 1:1 deionized water and anhydrous ethanol; microsphere preparation process parameters: sodium alginate viscosity 15-25 cP (1wt% in H 2 O), the concentration is 0.03g / ml, the extrusion rate of the microfluidic device is 0.3mL / h, the solution stirring rate is 40r / min, the microsphere aging time is 5min, the temperature is 25°C, the pH is 7.2, and the microspheres are washed 5 times with deionized water, each time for 3min), placed in a 300ng / ml BMP-2 solution for 10min for immersion adsorption to obtain the drug-loaded microsphere material, rinsed with deionized water and dried, and stored at 4°C for use;

[0057] 3) Prepare a 7.5 wt% DA-HAMA solution (0.25 wt% LAP, solvent: PBS) under light-proof and 60°C heating conditions, and add 0.5 wt% drug-loaded microspheres to the solution when it cools to room temperature and mix well;

[0058] 4) After degassing by low-speed centrifugation (500 rpm, 3 min), the mixed solution sterilized by irradiation, i.e., the adhesive, was injected into the bone defect area using a sterile injection device, and a handheld UV pen was used for in-situ UV curing (UV curing wavelength of 405 nm, power of 20 W, and time of 1 min) to achieve adhesion to the defect area, thereby achieving the purpose of bone repair.

[0059] Compared with Example 1, this example reduces the use of VEGF. The extract of the above material was prepared and co-cultured with BMSCs for 7 days. The results of CCK-8 showed that the cell survival rate was about 88.7%; the adhesion strength was about 31.1 kPa; it was injected into the skull defect model and fitted well with the defect area. After surgical suturing and feeding, sampling after 4 weeks found that the vascularization effect and bone repair effect of the defect area were average, and the new bone formation was worse than that in Example 1.

Claims

1. A method for preparing an in situ injectable bone repair adhesive material with dual sequential osteogenesis function, characterized in that: The following steps are involved: 1) Hyaluronic acid is double-grafted and modified with methacrylic anhydride and dopamine hydrochloride in sequence to obtain DA-HAMA biomacromolecules with UV curing and adhesion functions; 2) Preparation of Ca using microfluidic system 2+ Physically cross-linking sodium alginate microspheres, placing them in an osteogenic drug solution for immersion and adsorption to obtain drug-loaded microsphere materials; 3) preparing a DA-HAMA solution, adding angiogenic factors and the drug-loaded microspheres to the solution when the solution is cooled to room temperature, and mixing them evenly. After centrifugal degassing and irradiation sterilization, an in situ injectable bone repair adhesive material is obtained.

2. The method for preparing the in situ injectable bone repair adhesive material with dual sequential osteogenesis function according to claim 1, characterized in that: In step 1), the double chemical grafting modification of hyaluronic acid using methacrylic anhydride and dopamine hydrochloride in sequence is specifically that hyaluronic acid is first modified with methacrylic anhydride to obtain HAMA, and then HAMA is modified with dopamine hydrochloride.

3. The method for preparing the in situ injectable bone repair adhesive material with dual sequential osteogenesis function according to claim 2, characterized in that: In the process of modifying hyaluronic acid with methacrylic anhydride, hyaluronic acid is heated and dissolved in a PBS solution, methacrylic anhydride is slowly added dropwise, and after reacting for 2-3 hours, an equal volume of deionized water is added, and then hydrogen peroxide is slowly added dropwise to the solution, and after stirring for 30-60 minutes, it is dialyzed in the dark, and HAMA is obtained after freeze-drying; wherein the reaction temperature is 50-60° C., the stirring rate is 200-400 r / min, the hyaluronic acid has a molecular weight greater than 100,000 and a concentration of 3-8wt%, the methacrylic anhydride is added at a concentration of 2-6wt%, and the amount of hydrogen peroxide added is 1 / 10-1 / 5 of the total volume of the solution, the deionized water is dialyzed for 5-10 days, and the solution is changed 3-5 times a day.

4. The method for preparing the in situ injectable bone repair adhesive material with dual sequential osteogenesis function according to claim 2, characterized in that: In the process of modifying HAMA with dopamine hydrochloride, the HAMA and dopamine hydrochloride are dissolved in a DMSO / deionized water mixed solvent, EDC is added under nitrogen protection and stirred for activation for 30-60 minutes, and then NHS is added for coupling reaction, the obtained product is dialyzed in the dark, and lyophilized to obtain a dopamine-modified methacryloyl hyaluronic acid (DA-HAMA) biomacromolecule; the concentration of dopamine hydrochloride is 0.2-0.8wt%; the concentration of HAMA is 5-10wt%; the mixed solvent The ratio of the agent is 10wt% dimethyl sulfoxide (DMSO) / 90wt% deionized water; the concentration of the 1-ethyl-3[3-dimethylaminopropyl]carbodiimide hydrochloride (EDC) is 0.02-0.1wt%; the concentration of the N-hydroxysuccinimide (NHS) is 0.02-0.1wt%; the coupling reaction time is 12-24 hours; the stirring adopts magnetic stirring at 400-600 rpm; after the coupling reaction is completed, the product is dialyzed with deionized water in the dark for 5-7 days, and the solution is changed 3-5 times a day.

5. The method for preparing the in situ injectable bone repair adhesive material with dual sequential osteogenesis function according to claim 1, characterized in that: In step 2), the microfluidic system prepares Ca 2+ In the process of physically cross-linking sodium alginate microspheres, the channel diameter of the microfluidic system is 50-200 μm; the coagulation bath is 0.04-0.1 g / ml calcium chloride, and the volume ratio of the solvent system is 1:3-3:1 deionized water and anhydrous ethanol; the viscosity of the sodium alginate is 15-25 cP (1wt% in H2O), and the concentration is 0.02-0.04 g / ml; the extrusion rate of the microfluidic device is 0.1-1.0 mL / h, the solution stirring rate is 20-40 r / min, the microsphere aging time is 5-15 min, the temperature is 20-25°C, and the pH is 6.5-7.

5. After completion, the obtained microspheres are washed 3-5 times with deionized water, and each time lasts 3-5 min; During the immersion adsorption process, the osteogenic drug is one or more of bone morphogenetic protein-2 (BMP-2), osteogenic growth peptide (OGP), transforming growth factor β (TGF-β), danshensu, icariin, total flavonoids of Rhizoma Drynariae, paeoniflorin and total saponins of Panax notoginseng, with a concentration of 100 ng / ml-0.1 g / ml, and the immersion adsorption time is 5-15 min. After rinsing with deionized water, the drug is air-dried and stored for later use.

6. The method for preparing the in situ injectable bone repair adhesive material with dual sequential osteogenesis function according to claim 1, characterized in that: In step 3), during the preparation of the DA-HAMA solution, the DA-HAMA solution contains a photoinitiator, and the DA-HAMA preparation temperature is 60-80° C. and the concentration is 5-15wt% under light-proof and heating conditions. The photoinitiator is one or more of LAP, Irgacure, and photoinitiator 2959, and the concentration is 0.25-0.5wt%, and the solvent is PBS; The angiogenic drug is one or more of vascular endothelial growth factor (VEGF), angiopoietin-1 (Ang-1), QK peptide, deferoxamine, salvianolic acid B, astragaloside, ginsenoside, and paeoniflorin, with a concentration of 100 ng / ml-0.1 g / ml; The concentration of the drug-loaded microspheres is 0.5-5wt%; During the centrifugal degassing process, the rotation speed is 500-1000 rpm for 3-10 min.

7. An in situ injectable bone repair adhesive material with dual sequential osteogenesis function, characterized in that: The method is adopted as claimed in any one of claims 1 to 6.

8. A bone repair material, characterized in that: Comprising the bone repair adhesive material as described in claim 7.

Citation Information

Patent Citations

  • Bone repair material allowing injection of multi-pore structure and preparation method of bone repair material

    CN108744060A

  • Osteogenesis-promoting hydrogel microspheres with cell adhesiveness and preparation method thereof

    CN116099045A

  • Injectable composite filler and preparation method thereof

    CN118384329A

  • Mussel inspired nancomposite adhesives for biomedical applications

    US20210106718A1

  • Controlled heat delivery compositions

    WO2020243047A1

Cited By

  • In-situ adhesion gel filler with biofilm attacking and dual osteogenesis promoting functions as well as preparation method and application of in-situ adhesion gel filler

    CN121288013A

  • An in-situ adhesive gel filler with biofilm attack and dual osteoconductive functions and its preparation method and application

    CN121288013B

  • Biphase in-situ injection-mixing type hydrogel adhesive coating material with biological membrane breaking and killing function and preparation method of biphase in-situ injection-mixing type hydrogel adhesive coating material

    CN121288030A

  • Application of bis-glycine in preparation of medicine for treating aortic valve calcification, micro-nano particle and preparation method of micro-nano particle

    CN121445707A